The Utilization Of Culture Map Board Media To Improve Teachers 'Skills In Elementary School - Ni’mah Arindita, Mu’arifatun; Fathurohman, Irfai; Setiawan, Deka (Journal of Education Technology, 2020)
Lack of teacher skills in teaching and the lack of the use of instructional media lead to ineffective learning process. This study aims to improve the skills of teachers assisted by cultural map board media. This research was carried out by classroom action research. This research lasted for two cycles, which each cycle consists of four stages, including planning, implementing, observing and reflecting. Data collection techniques consisted of interviews using interview guidelines, as well as observation using teacher skills observation sheets and documentation. The data analysis technique used is qualitative and quantitative data. The results shows that the skills of the teacher assisted by the cultural map board media obtained an average in cycle I in percentage of 70% and increases in cycles II by 80% with good category. Based on the result of this study, it can be concluded that using the cultural map board media can improve the teachers’ skills in Elementary School.